Concurrence between the maxillary midline and bisector to the interpupillary line - Eskelsen, Evania; Fernandes, Camila Borges; Pelogia, Fernanda; Cunha, Leonardo Gonçalves; Pallos, Débora; Neisser, Maximiliano Piero; Liporoni, Priscila Christiane Suzy (Wiley, 2009)
Purpose: Symmetry is one of the factors that contributes to facial harmony, and in oral rehabilitation it determines the success of esthetic treatment. Therefore, the aim of the present study was to analyze the axial symmetry between the bipupillar midline and maxillary central incisors midline of 102 dental students (both genders) distributed across five Brazilian dental schools. Materials and Methods: Students with no teeth missing and who had never been subjected to any dental treatment were selected. Photographs were taken with a Dental Eye III camera with a 100-mm macro objective and ratio of 1 : 10 from natural size, recorded on an Ektachrome ASA/ISO 100 film. The images were developed and applied to Microsoft Office Power Point 2007 software. The results were analyzed by analysis of variance and Student's t-test (= 0.05). Results: There was no significant correlation between bipupillar midline and the maxillary dental midline, irrespective of gender. Conclusion: No significant coincidence was observed between the interpupillary and dental midline. However, the interpupillar distance and its relationship with other anatomic structures may be used as a reference in treatment, but measurements must be assessed individually. CLINICAL SIGNIFICANCE Anatomic measurements and facial proportions can be helpful during the planning of esthetic oral rehabilitation. © 2009 Wiley Periodicals, Inc.
Keywords: cephalometry; dental care; esthetics; eye; female; histology; human; image processing; incisor; male; maxilla; medical photography; methodology; nose; pupil; Cephalometry; Esthetics; Esthetics, Dental; Eye; Female; Humans; Image Processing, Computer-Assisted; Incisor; Male; Maxilla; Nose; Photography, Dental; Pupil